Pelatihan Digital Marketing Sebagai Model Bisnis Daring Bagi Kader PKK Desa Randusari, Desa Bangsalan dan Desa Salakan, Kecamatan Teras, Kabupaten Boyolali - Edwin Zusrony; Widyaningsih, Dewi; Sumarlin, Tantik; Santoso, Agustinus Budi; Adriana, Myra; Dianta, Indra Ava; Setiawan, Dwi (Lembaga Dongan Dosen, 2023)
The economic improvement of Indonesian society began to increase after the Covid-19 pandemic, which was supported by the household economy through the MSME industry. PKK (Family Welfare Empowerment) is an organization that drives development at the village level which has the main task of improving the quality of life of the community. STEKOM University, through a team of lecturers from across fields of science, tries to provide digital marketing training on making meeting invitation designs, designing MSME product promotions using the Canva application and product promotion via the